Rancang Bangun Sistem Informasi Profil TK Al Hidayah Kebumen dengan Metode Waterfall Berbasis Website - Saputro, Ragil Widodo; Yuminah, Yuminah (Jurnal Kridatama Sains dan Teknologi, 2022)
Al Hidayah Kindergarten does not yet have an information system that can be accessed through the website so the presentation of information is still done conventionally. This study aims to build a website-based school profile information system. This information system can be used by schools to improve the quality of information services to the community. The method used in this research is the waterfall model system development method because this method is the most suitable development model used by developers, system project work is easy to control and can be timely. The programming language that the author uses is PHP (Hypertext Preprocessor) and uses a MySQL database. Testing the feasibility of the system using blackbox testing. The functions tested are admin and user pages. The test results on the admin page obtained that 90% were declared successful, 10% were declared slow loading, and no failed test items were found. While on the user page 95% was declared successful, 5% was declared slow loading, and no failed test items were found. Keywords: information system, website, waterfall model, PHP, blackbox testing